5G: MIMO BDMA SYSTEM TRENDS AND TECHNOLOGY - Ashwaq Q. Hameed; Salman Goli; Zahraa Jaafar Oleiwi (QALAAI ZANIST JOURNAL, 2021)
Beam Division Multiple access (BDMA) is the last technique came to create the fifth-generation (5G) and solving the problem in the fourth generation (4G). In which base station (BS) allocates private beam to the mobile station (MS) in the system, to increase the capacity and bandwidth of system. For that antenna beam is divided according to the speed and location of mobile stations. In mobile wireless communication the important thing is how to increased limited frequency of the system, improve data rate and good quality of services for user etc. This paper presents information about BDMA and explains the different technologies, and which we want to making future mobile with more powerful and more in demand. Useful thing in BDMA technique is the large number of users to connect at the same time by direction of orthogonal beam from BS by giving multiple access to MS, and increasing the ability of system to be established very big channel. Direction of antenna beam goes off the desired location of MS, and void are placed in undesired direction depend on work environment.